Pengaruh Soft Skill dan Hard Skill terhadap Kesiapan Menjadi Guru pada Mahasiswa Pendidikan Ekonomi Angkatan 2021 Universitas Jambi: Penelitian - Cecilia Magdalena Manik; Fachruddiansyah Muslim; Destri Yaldi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of soft skills and hard skills on the readiness to become teachers of economic education students, class of 2021, Jambi University, both partially and simultaneously. This study is a quantitative approach with the ex-post facto method. The data collection technique uses Google Form. The data analysis technique used is descriptive statistical analysis. The population in this study were economic education students, class of 2021 with a sample of 84 respondents and taken by simple random sampling. Based on the results of the study, it shows that partially the soft skill variable has a positive and significant effect on the readiness to become teachers with a t count value> t table. Partially, the hard skill variable has a positive and significant effect on the readiness to become teachers with a t count value> t table. Simultaneously, Soft Skills and Hard Skills have a positive and significant effect on Readiness to Become Teachers.